Self-concept and its relationship to artistic taste among students of the College of Basic Education (Journal of the College of Basic Education, 2022)
The learner's self is the product of the experiences he goes through and his self-evaluation is gradually generated from a young age with the desire to sculpt the ideal self that he spoke of and often sought to achieve a realistic self that is in line with his capabilities and experiences and the degree of his adaptation to his environment instead of striving to achieve an ideal and unrealistic self that exploiting the capabilities Latent helps to develop the true self to that realism that achieves peace and harmony for the learner with himself and his environment. Therefore, art education has tended its activities to build the personality of the learner through the events of a desired change in the behavior of these changes that qualify him to perform his social functions and achieve a reasonable degree of self-balance.